Denosumab treatment in aneurysmal bone cyst: Evaluation of nine cases. Issue 4 (29th December 2017) - Kurucu, Nilgun; Akyuz, Canan; Ergen, Fatma Bilge; Yalcin, Bilgehan; Kosemehmetoglu, Kemal; Ayvaz, Mehmet; Varan, Ali; Aydin, Burca; Kutluk, Tezer
Abstract: Background: Aneurysmal bone cyst (ABC) is a benign bone tumor. Curettage and bone grafting is the common treatment. Here, we retrospectively evaluate nine patients treated with denosumab. Procedure: Nine patients with ABC, mostly pelvic and vertebral, treated with denosumab were analyzed retrospectively. A 70 mg/m 2 denosumab dose was used weekly in the first month, and then monthly. Clinical and radiological responses to treatment were evaluated. Results: In all patients, clinical symptoms including pain and limping regressed completely within 3 months. Radiological evaluation revealed changes in lesion size and content. In six patients, overall volume reduction in the range of 18–82% was detected. Decreases in the size and number of cysts were detected in eight patients. In five patients, fat signal appeared on follow‐up imaging. No major side effects were observed during treatment. Median follow‐up time after treatment was 15 months. At 5 months, severe hypercalcemia was observed in two patients due to rebound increase in osteoclastic activity. Subsequent to denosumab treatment, three patients underwent surgery for clinical or radiological recurrence. Conclusions: Our results showed that denosumab provided a meaningful clinical and radiological improvement in ABC. It may be a treatment option, especially in spinal and pelvic tumors with potentially high surgical morbidity. However, late rebound hypercalcemia may restrict its use. Studies with more cases are required for routine use of denosumab in ABC.